Modulating the import of medium-chain alkanes in E. coli through tuned expression of FadL. Issue 1 (December 2016) - Call, Toby; Akhtar, M.; Baganz, Frank; Grant, Chris
Abstract Background In recent years, there have been intensive efforts to develop synthetic microbial platforms for the production, biosensing and bio-remediation of fossil fuel constituents such as alkanes. Building predictable engineered systems for these applications will require the ability to tightly control and modulate the rate of import of alkanes into the host cell. The native components responsible for the import of alkanes within these systems have yet to be elucidated. To shed further insights on this, we used the AlkBGT alkane monooxygenase complex fromPseudomonas putida GPo1 as a reporter system for assessing alkane import inEscherichia coli . Two nativeE. coli transporters, FadL and OmpW, were evaluated for octane import given their proven functionality in the uptake of fatty acids along with their structural similarity to theP. putida GPo1 alkane importer, AlkL. Results Octane import was removed with deletion offadL, but was restored by complementation with afadL -encoding plasmid. Furthermore, tuned overexpression of FadL increased the rate of alkane import by up to 4.5- fold. A FadL deletion strain displayed a small but significant degree of tolerance toward hexane and octane relative to the wild type, while the responsiveness of the well-known alkane biosensor, AlkS, toward octane and decane was strongly reduced by 2.7- and 2.9-fold, respectively. Conclusions We unequivocally show for the first time that FadL serves as the major route for medium-chain alkane import inE. coli . The experimental approaches used within this study, which include an enzyme-based reporter system and a fluorescent alkane biosensor for quantification and real-time monitoring of alkane import, could be employed as part of an engineering toolkit for optimizing biological systems that depend on the uptake of alkanes. Thus, the findings will be particularly useful for biological applications such as bioremediation and biomanufacturing.